Proteome Analysis Reveals Distinct Mitochondrial Functions Linked to Interferon Response Patterns in Activated CD4+ and CD8+ T Cells - Gerner, Marlene C.; Niederstaetter, Laura; Ziegler, Liesa; Bileck, Andrea; Slany, Astrid; Janker, Lukas; Schmidt, Ralf L.J.; Gerner, Christopher; Del Favero, Giorgia; Schmetterer, Klaus G. (Frontiers in Pharmacology, 2019)
While genetic traits and epigenetic modifications mainly encode cell type-specific effector functions, the eventual outcome is also prone to modulation by post-transcriptional regulation mechanisms. T cells are a powerful model for the investigation of such modulatory effects, as common precursor cells may differentiate either to helper CD4+ T cells or cytotoxic CD8+ cells, which elicit distinct functionalities upon inflammatory stimulation. Human primary CD4+ and CD8+ T cells were purified from three individual donors and activated with anti-CD3/CD28 antibodies. Associated proteome alterations were analyzed by high-resolution mass spectrometry using a label-free shotgun approach. Metabolic activation was indicated by upregulation of enzymes related to glycolysis, NADH production, fatty acid synthesis and uptake as well as amino acid and iron uptake. Besides various inflammatory effector molecules, the mitochondrial proteins CLUH, TFAM and TOMM34 were found specifically induced in CD4+ T cells. Investigation of overrepresented conserved transcription binding sites by the oPOSSUM software suggested interferon type I inducer IRF1 to cause many of the observed proteome alterations in CD4+ T cells. RT qPCR verified the specific induction of IRF1 in CD4+ T cells only. While the interferon regulatory factor IRF4 was found induced in both T cell subtypes at protein and mRNA level, IRF9 and the type I interferon-induced proteins IFIT1, IFIT3 and MX1 were only found induced in CD4+ T cells. As oxidative stress enhances mitochondrial DNA-dependent type I interferon responses, the present data suggested that mitochondrial activities regulate those cell type-specific signaling pathways. Indeed, we detected mitochondrial superoxide formation predominantly in CD4+ T cells by live cell imaging with confocal microscopy and via FACS analysis with MitoSOX™. As interferon signaling regulates important features such as resistance regarding immune checkpoint blockade therapy, the present data may identify potential new targets for the efficient control of highly relevant immune cell properties.